Each peach pear plum: an "I spy" story (An I-spy-book, ,, 1979)
Tom Thumb, Jack and Jill, Baby Bunting, and a host of other familiar nursery-rhyme characters are hiding in the colorful pictures, and children are challenged to find them as the story unfolds.

I spy extreme challenger: a book of picture riddles (I spy books, ,, 2000)
Rhyming text leads readers to find objects hidden in the photographs of toys, animals, food, and utensils.
Yikes! , Masquerade , The laughing clown , Old-fashioned school , Odds & ends , A secret cupboard , Christmas crafts , The mysterious monster , Creepy crawly cave , Make believe , Monster Workshop , The toy box solution , Extra credit riddles.